PENERAPAN PROGRAM KESELAMATAN KERJA PADA FORKLIFT DI PT ALP PETRO INDUSTRY - Mochammad Angga Tri Tjahyo Adhy (Universitas Airlangga, 2017)
Forklift is one of lift and transport aircraft that support the implementation of the production process which consist high enough of hazards, and there is a possibility of work accidents. So the prevention efforts should be made with fulfill their safety requrements, to prevent that accidents.The purpose of this study were learning the programs of health and safety of the operation forklift in PT ALP Petro Industry Gempol, Pasuruan. This study was an observational descriptive study with cross-sectional approach. The subjects were all of the forklift operator, safety officer and supervisor, and factory general supervisor.The variables were studied were license of safety, safety tools, housekeeping, maintenance, inspection, safety sign, and wearing personal protective equipment.The primary data were obtained by using observations and interviews, and the secondary data were obtained from the company. Furthermore, the data was processed descriptively. The results showed that there are six programs have been implemented in accordance with applicable regulations, and there is oneprogram that hasn’t been accomplished in accordance with the relevant regulations that safety signs. Keywords: safety programs, forklift